2010
DOI: 10.1080/1745039x.2010.511517
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different doses of free 𝛂-linolenic acid infused to the duodenum on the immune function of lactating dairy cows

Abstract: This study investigated the effect of a duodenal infusion of a C18:3 free fatty acid on the immune function of lactating dairy cows. Four primiparous Chinese Holstein cows fitted with duodenal cannulas received 0, 100, 200, 300, and 400 g/d of alpha-linolenic acid (LNA) in a two-treatment crossover design. Blood was collected and serum IgA, IgG, IgM, prostaglandin E2 (PGE2) and Th1/Th2 cytokines were determined. Results showed that increasing the supply of LNA to the small intestine of dairy cows linearly incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 27 publications
0
17
1
Order By: Relevance
“…Decreases in DMI indicate changes in the metabolism of cows, which were associated with gut hormones, including increased plasma concentrations of glucagon-like peptide-1 (7-36) amide and cholecystokinin, a decreased insulin concentration, as well as with altered plasma metabolites, including increased concentrations of non-esterified fatty acids and decreased concentration of cholesterol (Litherland et al, 2005;Relling and Reynolds, 2007). In addition, concentrations of prostaglandin E2 also declined, whereas plasma IgG levels rose linearly with increasing duodenal infusion doses of LNA (Sun et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Decreases in DMI indicate changes in the metabolism of cows, which were associated with gut hormones, including increased plasma concentrations of glucagon-like peptide-1 (7-36) amide and cholecystokinin, a decreased insulin concentration, as well as with altered plasma metabolites, including increased concentrations of non-esterified fatty acids and decreased concentration of cholesterol (Litherland et al, 2005;Relling and Reynolds, 2007). In addition, concentrations of prostaglandin E2 also declined, whereas plasma IgG levels rose linearly with increasing duodenal infusion doses of LNA (Sun et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In attempts to study the underlying mechanisms of LNA transport to milk and modification of the fatty acid composition, LNA has been infused post-ruminally to avoid ruminal biohydrogenation (Khas-Erdene et al, 2010;Cô rtes et al, 2011). Interestingly, we found that increasing the LNA content of milk through post-ruminal infusion was accompanied by reduced oxidative stability of the milk fat and suppressed immune function of the cows as revealed using the ELISA method (Sun et al, 2010).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Lower concentrations of PGE2 and IFN-γ were observed in dairy heifers that were fed diet supplemented with FLL was better than the other three groups. From the results of the published articles, it could be concluded that PGE2 is very important to regulate the development and roles of immune cells and to synthesis immunity regulatory cytokines (Calder, 1999;Yi et al, 2005aYi et al, , 2005bSun et al, 2010;Chen et al, 2003;Liu et al, 2003). It was reported that when animals suffered from acute or chronic inflammation or pathogens challenge, relatively higher concentrations of PGE2 and/or IFN-γ will be secreted into blood (Kinsella et al, 1990;carter and Dutton, 1996;Desmedt et al, 1998).…”
Section: Immunitymentioning
confidence: 99%
“…Observations in chicks Chen et al, 2003;Yi et al, 2005a), piglets (Liu et al, 2003;Yi et al, 2005b) and dairy cows (Sun et al, 2010;Zhang et al, 2004Zhang et al, , 2005 from the published literature indicated that when animals were in good immunity status, they showed a relatively higher productive performance. Some clinical therapies in persons also demonstrated that some Chinese herbs including RA, RC, and FLL have capability to improve immunity status (Tang et al, 2003).…”
Section: Immunitymentioning
confidence: 99%